Characterization of twisted wave in indoor multipath environment - Wong, Bing Cheng (2018)
With the advancement of technology, wireless communication channel is becoming increasingly congested. There is thus a need for an alternative technique in better handling of the available bandwidth. Therefore, twisted Radio Wave, in particular, has attracted lots of attention over the past few years due to the unique properties of being able to transmit multiple channels of data through a single frequency. This approach uses a phase manipulation technique known as Orbital Angular Momentum (OAM), and when operating at different OAM modes provides many degrees of freedom. Thus, Twisted Radio Wave will serve as the ideal carrier frequency to overcome the bandwidth limit. This project is a continuation of previous student work where they have tested out the concept of generating twisted radio wave using multiple dipole antenna elements arranged in a circular array. However, the MATLAB programme structure is hardcoded to examine the waveform along a fixed propagation axis and antenna polarisation. Thus, a more comprehensive simulation requires the development of a new coding framework with more functionalities and support for future expansion. In this report, simulation results of twisted radio wave will be evaluated along with the newly implemented features such as antenna polarisation control, ground plane reflector, and pivoting of source and field antenna plane. The simulation results are then analysed from the different perspective such as phase plot, intensity plot and directivity plot. Furthermore, a 3D non-circular array knows as icosahedron were used to map the antenna array element into the different plane where the results show that twisted radio wave generation is not just limited to the circular array shape. Besides, a Graphical User Interface (GUI) is designed and developed to facilitate interaction, prevent any accident change of source code and will provide prompt when the input parameters are invalid.